European Dimension of the Constitutionof the Republic of Poland of 2 April 1997 - Bisztyga, Andrzej (1964- ); Wojtczak, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper discusses the Constitution of the Republic of Poland of 2 April 1997 and its European dimension, including the analysis of its significance, implications and evolution in the context of Poland`s integration with the European Union. The authors note significant changes in the constitutional practice in recent years with regard to the interpretation and application of the provisions of the Constitution of the Republic of Poland. Constitutional laws are acquiring new interpretations, while certain aspects of the Constitution are hardly applied at all. The study also shows the role of the Polish Constitutional Tribunal and the judgments of the Court of Justice of the European Union in the context of European integration.
Keywords: Konstytucja Rzeczypospolitej Polskiej; Unia Europejska; zasady konstytucyjne; the Constitution of the Republic of Poland; European Union; constitutional principles